Parità di genere e professioni legali. Una lunga storia... - Bianchi Riva, Raffaella; Spaccapelo, Chiara (Milano University Press, 2023)
This volume was born out of the encounter between academia and the professional environment, in order to contribute, from different points of view and from a diachronic perspective, to the issue of gender equality in the legal profession. In light of the differences still existing, the contributions address some of the main issues related to women's access to the advocacy and the judiciary, from historical and current points of view, within the broader framework of the implementation of the constitutional principle of equality. It aims at promoting a culture of equality, i.e. a culture capable of moving not only on the level of homogeneity, but also on the level of diversity, enhancing the characteristics of each person-professional, in a pluralistic and inclusive perspective.